Survival of Filamentous Cyanobacteria Through Martian ISRU: Combined Effects of Desiccation and UV-B Radiation - Miguel Arribas Tiemblo; Inês P. E. Macário; Antonio Tornero; Ana Yáñez; Slavka Andrejkovičová; Felipe Gómez (Microorganisms)
Cyanobacteria are a widespread group of photosynthesizing prokaryotes potentially relevant for space exploration, as they can produce both oxygen and organic matter. These organisms have been repeatedly proposed as tools for colonizing planetary bodies in the solar system. We used several Martian regolith simulants to support the growth of three widespread filamentous cyanobacteria (Desmonostoc muscorum UTAD N213, Anabaena cylindrica UTAD A212 and an uncharacterized Desmonostoc sp.). All cyanobacteria grew well on the surface of the commercial simulants MGS-1 and MMS-2 and in soluble extracts obtained from them, suggesting that these Martian regolith analogs contain everything necessary to sustain cyanobacterial growth, at least in the short term. We also evaluated the survival of the two Desmonostoc species under desiccation and UV-B radiation, using the same regolith simulants and two clays: Montmorillonite and nontronite. Desiccation hindered growth, but both cyanobacteria were able to recover in less than 30 days in all cases after desiccation. Short irradiation times (up to 1000 kJ/m2) did not consistently affect survival, but longer ones (24,000 kJ/m2) could fully sterilize some samples, although cyanobacteria within MGS-1, montmorillonite and nontronite showed signs of recovery in the long term (>70 days). Clays led to very fast recoveries, particularly montmorillonite.